Changes in central venous oxygen saturation, lactates, and ST segment changes in a V lead ECG with changes in hemoglobin in neurosurgical patients undergoing craniotomy and tumor excision: A prospective observational study - Liby G Pappachan; Aparna Williams; Tunny Sebastian; Grace Korula; Georgene Singh (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: The aim of the study was to observe the trends in central venous oxygen saturation (ScvO2), lactate, and ST segment changes with change in hemoglobin in patients undergoing acute blood loss during surgery and to assess their role as blood transfusion trigger. Material and Methods: Seventy-seven consecutive patients undergoing craniotomy at a tertiary care institution were recruited for this study after obtaining written, informed consent. After establishing standard monitoring, anesthesia was induced with standard anesthetic protocol. Hemodynamic parameters such as heart rate, blood pressure (mean, systolic, diastolic), pulse pressure variation (PPV), and physiological parameters such as lactate, ScvO2, ST segment changes were checked at baseline, before and after blood transfusion and at the end of the procedure. Statistical Analysis: Comparison of the mean and standard deviation for the hemodynamic parameters was performed between the transfused and nontransfused patient groups. Pearson correlation test was done to assess the correlation between the covariates. Receiver operating characteristic (ROC) curve was constructed for the ScvO2variable, which was used as a transfusion trigger and the cutoff value at 100% sensitivity and 75% specificity was constructed. Linear regression analysis was done between the change in hemoglobin and the change in ScvO2and change in hemoglobin and change in the ST segment. Results: There was a statistically significant positive correlation between the change in ScvO2and change in hemoglobin during acute blood loss with a regression coefficient of 0.8 and also between change in ST segment and hemoglobin with a regression coefficient of -0.132. No significant change was observed with lactate. The ROC showed a ScvO2cutoff of 64.5% with a 100% sensitivity and 75% specificity with area under curve of 0.896 for blood transfusion requirement. Conclusions: We conclude that ScvO2and ST change may be considered as physiological transfusion triggers in patients requiring blood transfusion in the intraoperative period.